Adenocarcinoma of sweat gland: case report and review of literature - Ekka, Nishith M. Paul; Bodra, Pankaj; Malua, Shital; Jha, Rohit Kumar (International Journal of Research in Medical Sciences, 2017)
Sweat gland carcinoma is a rare malignant tumour, first described in 1865, with approximately 220 cases reported in last 30 years. Lower limbs are the most common site of involvement, followed by the upper extremities, and the head. Trunk is rarely involved. Five histological types have been described, most common being porocarcinomas followed by ductal carcinomas, adenoid cystic carcinomas, syringomatous carcinomas and mucinous carcinomas. These are aggressive tumours with potential for distant metastasis. Wide surgical excision is the treatment of choice and the overall prognosis is poor. Here we report another case of sweat gland adenocarcinoma with no evidence of metastasis.